The impact of Acacia saligna on the composition and structure of the Mediterranean maquis. Issue 1 (3rd April 2021) - Tozzi, Francesco Pio; Carranza, Maria Laura; Frate, Ludovico; Stanisci, Angela
ABSTRACT: We evaluated the ecological impacts of the invasive alien species (IAS) Acacia saligna on the vegetation composition and structure of two coastal dunes woody habitats of Union concern (2250*: coastal dunes with Juniperus spp. and 2260: dunes with sclerophyllous vegetation consisting of Cisto-Lavanduletalia ). We sampled 20 paired plots per habitat type under invaded ( A. saligna cover > 70%) and non-invaded conditions, following a stratified random protocol. We tested the differences between invaded and non-invaded plots in terms of species composition of the entire species pool and of different ecological guilds and growth forms. Our findings showed that the invaded maquis (habitat 2260) had a significant decline in median richness (5 vs 2) and median cover (24.50 vs 8.00) of focal species and a significant increase in median cover of ruderal species (2.00 vs 5.50). The invaded juniper shrubs (EU habitat 2250*) preserved the typical species composition, but with significant variations in vegetation structure. The approach adopted in this study, accompanied by the results obtained, contribute towards fulfilling EU Regulation 1143/2014 on IAS. Key policy insights Results reveal worrying levels of biodiversity loss on coastal dunes due to the invasion of the invasive alien species (IAS) Acacia saligna. We detected remarkable changes in the physiognomy of the Mediterranean maquis coastal dunes – a landscape that is losing its biological uniqueness. The spread of A. saligna is having negative ecological effects upon the conservation status of two habitats of Union concern (codes 2250* and 2260). Urgent preventive measures, effective control strategies and eradication of A. saligna must be implemented across the Mediterranean Nature 2000 Coastal Protected Areas Network. The approach adopted and results obtained contribute to fulfilling EU Regulation 1143/2014 on IAS.